Youth Knowledge on the Concept and Activity Related To Human Capital - Wan Zulkifli, Wan Ainal Yaqin (2008)
The study was carried out to examine youth’s knowledge on the concept and activity related to human capital. The youth are the main asset of our nation and this group will be the future country’s leadership. It is important to prepare a high quality workforce of youth through the implementation of activities designed to enhance the existing knowledge of human capital amongst the youth and provide them with sufficient knowledge and skills to face an era of globalization. Therefore the main objective of this study was to examine the youth’s knowledge on the concept of human capital. Besides that, the objective of this research was also to identify what motivate and hinder youth from knowing about the concept of human capital. The study was conducted in Kuantan, Pahang from the period of May 19th 2007 till June 30th 2007. A total of 297 respondents consisting of youth within the ages 17 to 25 years in age were sampled. To fulfill the objectives of the study questionnaires were used to get information about the background and basic knowledge of the respondents on the concept and activities related to human capital, while FGD was carried out to support the research findings. The results from the study showed that the respondents possessed knowledge on human capital. The main sources quoted by most of the respondents as the channel with which they gained knowledge of human capital was from television, newspapers, friends, radio, formal classes, speeches, meetings, internet, signboards and through society agents. The obstacles that the respondents faced were lack of exposure of human capital concept, lack of inquisitiveness of respondents, low interest in the progress of current issue and also the respondents do not know the meaning of human capital itself. As a conclusion, knowledge on the concept and activity is extremely important for the youth to attract their interest to be involved in activities conducted. Efforts to empower youth through activities related to human capital development can be instrumental in producing youth with high standards of morality, quality, spiritual value and obedience. These qualities play an essential role in increasing the involvement of youth in the community towards the development of the nation both in the present and in the future.